2014
DOI: 10.3390/su6107142
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Effectiveness of the “Great Green Wall” as an Adaptation to the Effects of Climate Change and Desertification in the Sahel

Abstract: Abstract:The Great Green Wall (GGW) has been advocated as a means of reducing desertification in the Sahel through the planting of a broad continuous band of trees from Senegal to Djibouti. Initially proposed in the 1980s, the plan has received renewed impetus in light of the potential of climate change to accelerate desertification, although the implementation has been lacking in all but two of 11 countries in the region. In this paper, we argue that the GGW needs modifying if it is to be effective, obtain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 67 publications
0
29
1
Order By: Relevance
“…Already the benefits from year 1 are the harvesting of edible grass seeds and the collecting of fodder from the plots (quantitative data not shown). These results are in contrast to several previous concepts of a “line of trees” and emphasize the need to also plant shrubs and grass as an alternative, while complementing the current focus on trees (Escadafal et al ; O'Connor & Ford ). Our interventions aim to improve plant biodiversity and increase community involvement.…”
Section: Discussioncontrasting
confidence: 99%
“…Already the benefits from year 1 are the harvesting of edible grass seeds and the collecting of fodder from the plots (quantitative data not shown). These results are in contrast to several previous concepts of a “line of trees” and emphasize the need to also plant shrubs and grass as an alternative, while complementing the current focus on trees (Escadafal et al ; O'Connor & Ford ). Our interventions aim to improve plant biodiversity and increase community involvement.…”
Section: Discussioncontrasting
confidence: 99%
“…Experimental field trials have already been used and are currently being scaled out, to inform GGW decision makers as to how to increase biodiversity along the GGW path (Wade et al 2018). It has also recently been suggested that planting fast growing and/or flowering shrubs (the latter to support apiculture) in addition to trees could also diversify environmental and social benefits (O'Connor and Ford 2014). Of equal importance is understanding how tree species combinations provide response diversity to insure ES delivery.…”
Section: Research Area 3: Identification Of Actions and Their Socialmentioning
confidence: 99%
“…So far, the initiative has focused more on tree planting. O'Connor and Ford (2014) propose that planting 5 shrubs which will improve grazing areas by Nitrogen fixation rather than trees may have a more sustainable approach to the initiative. Nitrogen fertilizer application methods that reduce the formation of NO x from soil processes are used in the USA (Robertson et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The green wall initiative in Africa which covers most parts of the arid steppe climate zone often referred to as the Sahel and parts of the arid desert zone was launched in 2008 to restore ecosystem productivity and vitality to the Sahel while curbing the southward encroachment of the Sahara (O'Connor and Ford, 2014;Berrahmouni et al, 2014;UNCCD, 2016). Since its inception, the green wall initiative has seen millions of trees planted successfully (Berrahmouni et al, 2014) 5 and others nourished with fertilizers.…”
Section: Climate-based No 2 and Soil Moisture Anomalies Normalised Tmentioning
confidence: 99%